PENGARUH PERSEDIAAN BAHAN BAKU DAN TENAGA KERJA TERHADAP VOLUME PRODUKSI PADA PT BUKIT INTAN ABADI DI MEDAN - Aisyah, Siti; Rangkuti, Sahnan; Antoro, Budi (Bisnis-Net, 2024)
The availability of sufficient raw materials of good quality and support from qualified and highly committed workers will significantly determine the achievement of the targeted production volume. PT. Bukit Intan Abadi, as the locus of this research, is a company engaged in the wood sector with plywood as its main product. This study intends to determine the effect of raw material supply and labor on PT Bukit Intan Abadi production volume. This quantitative study uses data collection techniques carried out by observation, documentation studies, interviews, and questionnaires, with multiple linear regression data analysis techniques, t-tests, F-tests, and determination tests. The survey results with the t-test showed that the t-value of the raw material inventory variable was 4.526 t-count> t-table (4.526> 1.66757). The raw material inventory variable positively and significantly affects PT Bukit Intan Abadi Belawan's production volume. Furthermore, for the labor variable, the t-count value is known (13,322> 1.66757). It means that the labor variable positively and significantly affects production volume. Meanwhile, the results of the F test show that the F-count value is 96,330 compared to F-table 3.13, so F-count> F-table (96,330> 3.13). This means that the raw material and labor inventory variables positively affect PT Bukit Intan Abadi's production volume. Furthermore, the results of the determination test show that the R Adjust Square value is 0.742 or 74.2%. This means that raw materials and labor inventory can affect production volume by 74.2%, while the rest is influenced by other factors that have yet to be studied